Actin Dynamics at the T Cell Synapse as Revealed by Immune-Related Actinopathies - Dupré, Loïc; Boztug, Kaan; Pfajfer, Laurène (Frontiers in Cell and Developmental Biology, 2021)
The actin cytoskeleton is composed of dynamic filament networks that build adaptable local architectures to sustain nearly all cellular activities in response to a myriad of stimuli. Although the function of numerous players that tune actin remodeling is known, the coordinated molecular orchestration of the actin cytoskeleton to guide cellular decisions is still ill defined. T lymphocytes provide a prototypical example of how a complex program of actin cytoskeleton remodeling sustains the spatio-temporal control of key cellular activities, namely antigen scanning and sensing, as well as polarized delivery of effector molecules, via the immunological synapse. We here review the unique knowledge on actin dynamics at the T lymphocyte synapse gained through the study of primary immunodeficiences caused by mutations in genes encoding actin regulatory proteins. Beyond the specific roles of individual actin remodelers, we further develop the view that these operate in a coordinated manner and are an integral part of multiple signaling pathways in T lymphocytes.